Close your eyes and see it - Beth (Farol, 2021)
Beth Moysés, through her memories, narrates her artistic proposals made since 1994 in Brazil and abroad. With a wealth of details she describes her works, as objects, photographs, videos, installations and performances with which she has been articipating in individual and collective exhibitions, in curatorships that revolve around issues about women, feminism and omestic violence. Her immersion in language led her to work with artistic collectives, with volunteer women, many of them ictims of violence in ollaboration with Shelter from around the world.